Individualized Medicine : Ethical, Economical and Historical Perspectives - Fischer, Tobias; Langanke, Martin; Marschall, Paul; Michl, Susanne (Advances in Predictive, Preventive and Personalised Medicine,, 2015)
In 2009 the University Medicine Greifswald launched the "Greifswald Approach to Individualized Medicine" (GANI_MED) to implement biomarker-based individualized diagnostic and therapeutic strategies in clinical settings. Individualized Medicine (IM) has led not only to controversies about its potentials, but also about its societal, ethical and health economic implications. This anthology focusses on these areas and includes - next to clinical examples illustrating how the integrated analysis of biomarkers leads to significant improvement of therapeutic outcomes for a subgroup of patients - chapters about the definition, history and epistemology of IM. Additionally there is a focus on conceptual philosophical questions as well as challenges for applied research ethics (informed consent process, the IT-based consent management and the handling of incidental findings). Finally it pays attention to health economic aspects.  The possibilities of IM to initiate a paradigm shift in the German health care provision are investigated. Furthermore, it is asked whether the G-DRG system is ready for the implementation of such approaches into clinical routine.